Choose the Neighbor before the House: Agglomeration Externalities in a UK Science Park. (16th December 2017) - Helmers, Christian
Abstract: This article investigates the presence of agglomeration externalities and their effect on innovative activity of companies located in a science park in the UK. We analyze whether close geographical, industrial and technological proximity of firms located in a science park increases firm-level innovative activity measured as patenting. The results provide evidence for the presence of positive inter- and intra-industry knowledge spillovers among firms that are located in very close geographic proximity. The results suggest that knowledge spillovers decay rapidly with geographic distance even within small clusters of firms such as a science park.